Virtual YouTuber (VTuber) sebagai Konten Media Pembelajaran Online - Dhanar Intan Surya Saputra; Iwan Setyawan (Prosiding SISFOTEK, 2021)
Learning media is a tool for teaching and learning that can influence whether a teaching and learning succeeds or fails. Following technical advances and societal or student situations, there must be innovation in the development of learning media. As in the case of the Covid-19 Pandemic, where nearly all of the teaching and learning takes place online. Using VTuber (Virtual YouTuber) as content in online learning media is one of the innovations that can be implemented. Virtual avatars in the form of 2D (two-dimensional) or 3D (three-dimensional) avatars are used to construct VTuber, an online talent entertainer. Face and hand tracking technology can make VTuber feel like he or she is interacting with students, making teaching and learning processes less boring. The notion of VTuber was created as a learning media material in this study. The VTuber concept is hoped to be used at all levels of education, from elementary school through university, because animation appeals to people of all ages. Of course, story ideas must be tailored to the learning subject, and humorous anecdotes or jokes must be included to keep the online class setting lively.